2016
DOI: 10.3390/min6020029
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Characteristics of Late Permian Coals from the Yueliangtian Coal Mine, Guizhou, Southwestern China

Abstract: This paper reports the mineralogical compositions of super-low-sulfur (Yueliangtian 6-upper (YLT6U)) and high-sulfur (Yueliangtian 6-lower (YLT6L)) coals of the Late Permian No. 6 coal seam from the Yueliangtian coal mine, Guizhou, southwestern China. The mineral assemblages and morphology were detected and observed by X-ray diffractogram (XRD), optical microscopy and field-emission scanning electron microscope (FE-SEM) in conjunction with an energy-dispersive X-ray spectrometer. Major minerals in the coal sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Mo and U are enriched, while V According to the enrichment classification proposed by Dai et al [7], elements V, Cr, Mo, and U in the Ganhe coals are all significantly enriched (i.e., 10 < concentration coefficient (CC) < 100, CC referring to the ratio of a given trace element in an investigated sample versus the corresponding average for world hard coals reported by Ketris and Yudovich [46] The results of our EMPA analysis of Rongyang coal are shown in Figure 5 and Table 3 These data show that U-bearing minerals include anatase, clay minerals, guadarramite, and pyrite ( Figure 5), and that anatase coexists with clay minerals (Figure 5a). There are also traces of corrosion in anatase, indicating that coal has been subjected to hydrothermal fluids during syngenetic or early diagenetic stages [55]. Anatase also contains traces of Na, Mg, P, S, K, Ca, Fe, and, to a lesser extent, Cl, I, Nb, and U, and have a UO 2 content of 2.76% ( Table 3: spot 1).…”
Section: Trace Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mo and U are enriched, while V According to the enrichment classification proposed by Dai et al [7], elements V, Cr, Mo, and U in the Ganhe coals are all significantly enriched (i.e., 10 < concentration coefficient (CC) < 100, CC referring to the ratio of a given trace element in an investigated sample versus the corresponding average for world hard coals reported by Ketris and Yudovich [46] The results of our EMPA analysis of Rongyang coal are shown in Figure 5 and Table 3 These data show that U-bearing minerals include anatase, clay minerals, guadarramite, and pyrite ( Figure 5), and that anatase coexists with clay minerals (Figure 5a). There are also traces of corrosion in anatase, indicating that coal has been subjected to hydrothermal fluids during syngenetic or early diagenetic stages [55]. Anatase also contains traces of Na, Mg, P, S, K, Ca, Fe, and, to a lesser extent, Cl, I, Nb, and U, and have a UO 2 content of 2.76% ( Table 3: spot 1).…”
Section: Trace Elementsmentioning
confidence: 99%
“…The results of our EMPA analysis of Rongyang coal are shown in Figure 5 and Table 3 These data show that U-bearing minerals include anatase, clay minerals, guadarramite, and pyrite ( Figure 5), and that anatase coexists with clay minerals (Figure 5a). There are also traces of corrosion in anatase, indicating that coal has been subjected to hydrothermal fluids during syngenetic or early diagenetic stages [55]. Anatase also contains traces of Na, Mg, P, S, K, Ca, Fe, and, to a lesser extent, Cl, I, Nb, and U, and have a UO2 content of 2.76% ( Table 3: spot 1).…”
Section: Mineralogymentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrite is a common mineral in the Lopingian coal seams in southwestern China [8,39,[42][43][44]. From the K1 to K10 coal LTA residues, the proportion of pyrite increases gradually, from 2.7% (K3-1) to 20.4% (K10-5) and with an average of 10.5%.…”
Section: Pyritementioning
confidence: 99%
“…A number of studies showed that hydrothermal fluids have significantly influenced the geochemical and mineralogical composition of Lopingian coals in southwestern China (e.g., [26,48,86,[93][94][95]). The evidence for the No.…”
Section: Injection Of Multi-stage Hydrothermal Fluidsmentioning
confidence: 99%